Adapting EUROMOD for use in a developing country: The case of South Africa and SAMOD - Kate Wilkinson (University of Essex, Institute for Social and Economic Research (ISER), 2009)
This paper describes the construction of a microsimulation model for South Africa (SAMOD), which is based upon the EUROMOD platform. The paper discusses the need for a new microsimulation model in South Africa, the reasons why EUROMOD was a particularly suitable candidate as a basis for the new model and the challenges encountered in building the model. The intention of this paper is to provide necessary background material on the construction of the model to anyone wishing to work with SAMOD and to record the lessons learned in the model-building process which may be helpful to those considering developing their own microsimulation models in other countries. Particular attention is given to the way that South Africa, as a developing country, raises challenges that have not previously been encountered in the development of EUROMOD.
Keywords: I32; I38; H24; 330; tax-benefit policy; microsimulation; developing country; South Africa; Haushaltseinkommen; Armut; Einkommensumverteilung; Mikrosimulation; Südafrika